2021
DOI: 10.1101/2021.07.21.453198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fixation probabilities in network structured meta-populations

Abstract: The effect of population structure on evolutionary dynamics is a long-lasting research topic in evolutionary ecology and population genetics. Evolutionary graph theory is a popular approach to this problem, where individuals are located on the nodes of a network and can replace each other via the links. We study the effect of complex network structure on the fixation probability, but instead of networks of individuals, we model a network of sub-populations with a probability of migration between them. We ask h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Studying the effect of spatial structure on early adaptation in rugged fitness landscapes is an interesting topic for future work. Indeed, complex spatial structures with asymmetric updates or migrations impact the probabilities of fixation of mutations [61][62][63][64][65], which should affect early adaptation. Beyond the weak mutation regime, fitness valley crossing by tunneling can aid adaptation [56,57], which may especially impact subdivided populations, as first discussed in Wright's shifting balance theory [1,66] and shown in a minimal model [67].…”
Section: Discussionmentioning
confidence: 99%
“…Studying the effect of spatial structure on early adaptation in rugged fitness landscapes is an interesting topic for future work. Indeed, complex spatial structures with asymmetric updates or migrations impact the probabilities of fixation of mutations [61][62][63][64][65], which should affect early adaptation. Beyond the weak mutation regime, fitness valley crossing by tunneling can aid adaptation [56,57], which may especially impact subdivided populations, as first discussed in Wright's shifting balance theory [1,66] and shown in a minimal model [67].…”
Section: Discussionmentioning
confidence: 99%
“…Equality holds for a well-mixed population which includes self-loops meaning that every individual can also replace itself. In a fully connected graph of subpopulations, where the migration rate is symmetric, and the population is homogeneously distributed among the subpopulations, the fixation probability of the update mechanisms such as MBBdd that reduce to update mechanisms in a graph of individuals is the same as the fixation probability of the equivalent well-mixed population under update mechanism Bd [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is an occasional migration to and from other geographical areas. In [10], it has been shown that for a particular update mechanism, the results of evolutionary graph theory [1] do not carry over into graphs of subpopulations. For example, a star-structured metapopulation does not always amplify selection — in some migration regimes, it suppresses selection.…”
Section: Categorising Update Mechanisms For Graphs Of Subpopulationsmentioning
confidence: 99%
See 2 more Smart Citations